Iris atrophy in sickle cell disease. Issue 7 (July 1986) - Acheson, R W; Ford, S M; Maude, G H; Lyness, R W; Serjeant, G R
Abstract : Iris atrophy, of unknown origin and believed to be secondary to the vaso-occlusive process of sickle cell disease, has been observed in 25 eyes of 22 patients (two SS disease, 20 SC disease). The crude prevalence was highest in males with SC disease, in whom 14.7% of patients were affected. Iris atrophy was closely associated with proliferative sickle retinopathy in the same eye. Analysis of haematological indices failed to reveal any significant differences between patients with and without iris atrophy. The characteristics and distribution of iris atrophy are described as well as the histopathology in one 68-year-old male patient with SS disease.